Transformer Model in Wide Frequency Bandwidth for Power Electronics Systems. (28th January 2013) - Gonzalez-Garcia, Carlos; Pleite, Jorge
Abstract : The development of the smart grids leads to new challenges on the power electronics equipment and power transformers. The use of power electronic transformer presents several advantages, but new problems related with the application of high frequency voltage and current components come across. Thus, an accurate knowledge of the transformer behavior in a wide frequency range is mandatory. A novel modeling procedure to relate the transformer physical behavior and its frequency response by means of electrical parameters is presented. Its usability is demonstrated by an example where a power transformer is used as filter and voltage reducer in an AC-DC-AC converter.